2021
DOI: 10.1002/biot.202100064
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐surface binding domains from Clostridium cellulovorans can be used for surface display of cellulosomal scaffoldins in Lactococcus lactis

Abstract: Engineering microbial strains combining efficient lignocellulose metabolization and high‐value chemical production is a cutting‐edge strategy towards cost‐sustainable 2nd generation biorefining. Here, protein components of the Clostridium cellulovorans cellulosome were introduced in Lactococcus lactis IL1403, one of the most efficient lactic acid producers but unable to directly ferment cellulose. Cellulosomes are protein complexes with high cellulose depolymerization activity whose synergistic action is suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
3
4
0
Order By: Relevance
“…Western blotting did not detect the presence of X2 on any of these three strains post incubation with purified X2, indicating that X2 cannot directly bind to cell surfaces ( Figure 4C ). This agrees well with a recent study ( Tarraran et al, 2021 ).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Western blotting did not detect the presence of X2 on any of these three strains post incubation with purified X2, indicating that X2 cannot directly bind to cell surfaces ( Figure 4C ). This agrees well with a recent study ( Tarraran et al, 2021 ).…”
Section: Resultssupporting
confidence: 94%
“…Although previous studies indicated that the X2 module might directly bind to the cell wall ( Kosugi et al, 2004 ), our in vitro protein-cell wall binding assay indicated that the X2 module protein could not directly bind to the cell wall ( Figure 4C ). This is consistent with a recent study that scaffoldins containing X2 domains derived from CpbA were not able to bind to the L. lactis surface ( Tarraran et al, 2021 ). Based on structural analysis of the X2 modules ( Mosbah et al, 2000 ), the surface of the X2 module is predominantly covered by hydrophilic amino acids and only contains a hydrophobic shallow groove, which could explain why the X2 module could not directly bind to the cell wall.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Native cellulolytic strategies (NCSs) aim at introducing and/or improving high-value product biosynthetic pathways into natural (hemi)cellulolytic strains (e.g., Clostridium cellulovorans, Clostridium thermocellum, Figure 1c) [5]. The purpose of recombinant cellulolytic strategies (RCSs) is to confer (hemi)cellulolytic ability to microorganisms with valuable product formation properties (e.g., Saccharomyces cerevisiae, Yarrowia lipolytica, lactic acid bacteria) and include heterologous cellulase expression [47,53,54] (Figure 1d). Current progress of NCSs benefits from recent development of efficient gene tools for manipulating a number of (hemi)cellulolytic bacteria (e.g., Caldicellulosiruptor bescii, C. cellulovorans, C. thermocellum, C. cellulovorans, Thermoanaerobacterium saccharolyticum) [55][56][57][58][59], and fungi (e.g., Myceliophthora thermophila) [60].…”
Section: 1%mentioning
confidence: 99%
“…Recombinant cellulolytic strategies have been severely hampered by some major issues: (i) the extreme complexity and sophistication of native cellulase systems (Xu et al, 2015;Leis et al, 2017;Bule et al, 2018;Galera-Prat et al, 2020) (together with the high recalcitrance of lignocellulosic substrates) makes it difficult to mimic their efficiency through minimal artificial enzyme mixtures/complexes; (ii) insufficient understanding of the mechanisms promoting cellulase secretion Wu, 2013, 2014;De Paula et al, 2019) as well as species-specific protein secretion mechanisms challenge rational engineering of recombinant cellulolytic strains. Heterologous expression of cellulases has frequently been associated with cell toxicity (Mingardon et al, 2011;Kovács et al, 2013;Tarraran et al, 2021), and/or cellulase proteolysis by the host (Mingardon et al, 2005(Mingardon et al, , 2011, and/or low levels of cellulase activity (Van Rensburg et al, 2012) and/or the activation of the unfolded protein response (Ilmén et al, 2011), and/or metabolic burden (Ding et al, 2018). Metabolic burden refers to perturbation of host metabolism by heterologous protein expression and is generally attributed to energetic costs and competition for gene transcription/protein translation cell machinery associated with production of heterologous cellulases which generally cause a decrease in growth efficiency (Van Rensburg et al, 2012).…”
mentioning
confidence: 99%